A time series of incubation experiments to examine the production and loss of CH3I in surface seawater. Issue 12 (2nd December 2014) - Shi, Qiang; Marandino, Christa; Petrick, Gert; Quack, Birgit; Wallace, Douglas
Abstract In order to investigate production pathways of methyl iodide and controls on emissions from the surface ocean, a set of repeated in vitro incubation experiments were performed over an annual cycle in the context of a time series of in situ measurements in Kiel Fjord (54.3°N, 10.1°E). The incubation experiments revealed a diurnal variation of methyl iodide in samples exposed to natural light, with maxima during day time and losses during night hours. The amplitude of the daily accumulation varied seasonally and was not affected by filtration (0.2 µm), consistent with a photochemical pathway for CH3I production. The methyl iodide loss rate at nighttime correlates with the concentration accumulated during daytime suggesting a first‐order loss mechanism (R2 = 0.29, p << 0.01). Daily (24 h) net production (Pnet) was similar in magnitude between in vitro and in situ mass balances. However, the estimated gross production (Pgross) of methyl iodide ranged from −0.07 to 2.24 pmol L−1 d−1 and was up to 5 times higher in summer than Pnet calculated from the in situ study. The large excess of Pgross over Pnet in summer revealed by the incubation experiments is a consequence of large losses of CH3I by as‐yet uncharacterized processes (e.g., biological degradation or chemical pathways other than Cl− substitution).